Papel de los comités de participación ciudadana en la gestión del gobierno municipal: Caso Municipio de Monterrey = Role of participating civic committees in managing municipality governments: The case of Monterrey Municipality. - Guillén, A.; Sáenz López, Karla Annett Cynthia; López, J. Fabián (Universidad Autónoma de Nuevo León, 2007)
Abstract. The fundamental basics of participating civic committees with regards to the governmental decision making at the municipality levels are described. An example and a practical case resulting from research on participation of these committees for the Monterrey municipality are provided. The role of these civic participating committees in good democratic functioning and correct achievement of the aims of the governmental plans for the enhancement and improvement of the sociopolitical, economical and environmental quality of citizen’s life are discussed.